Generalized Morphea following Radiotherapy for an Intracranial Tumor - Balegar, Shrenik (Indian J Dermatol, 2016)
Morphea is a localized scleroderma variety which can be circumscribed or generalized and is characterized by sclerotic plaques developing on trunk and limbs. Surgery and radiation have been implicated as etiological factors for the development of morphea. Majority of the radiation-induced morphea cases have occurred in patients with breast cancer. The affected areas have been generally restricted to the area of radiation and nearby surrounding area in most of the reported cases. We hereby report a case of a 27-year-old male who developed radiation-induced progressive generalized morphea after getting radiotherapy for an intracranial tumor. His condition improved after dexamethasone-cyclophosphamide pulse therapy. With increased incidence of cancer worldwide and radiotherapy as a modality of treatment, it is imperative to follow the patient and look for the development of morphea which itself is a debilitating disease.